Ascaris suum infection in juvenile pigs elicits a local Th2 response in a setting of ongoing Th1 expansion - Oser, Larissa; Midha, Ankur; Schlosser-Brandenburg, Josephine; Rausch, Sebastian; Mugo, Robert M.; Kundik, Arkadi; Elizalde-Velázquez, Luis E.; Adjah, Joshua; Musimbi, Zaneta D.; Klopfleisch, Robert; Helm, Christina S.; von Samson-Himmelstjerna, Georg; et al. (Frontiers in Immunology, 2024)
Ascaris spp. undergo extensive migration within the body before establishing patent infections in the small intestinal tract of humans and pigs. However, whether larval migration is critical for inducing efficient type 2 responses remains poorly understood. Therefore, we investigated systemic versus local adaptive immune responses along the hepato-tracheal migration of Ascaris suum during primary, single infections in conventionally raised pigs. Neither the initial invasion of gut tissue nor migration through the liver resulted in discernable Th2 cell responses. In contrast, lung-stage larvae elicited a Th2-biased pulmonary response, which declined after the larvae had left the lungs. In the small intestine, we observed an accumulation of Th2 cells upon the arrival of fourth-stage larvae (L4) to the small intestinal lumen. In parallel, we noticed robust and increasing Th1 responses in circulation, migration-affected organs, and draining lymph nodes. Phenotypic analysis of CD4+ T cells specifically recognizing A. suum antigens in the circulation and lung tissue of infected pigs confirmed that the majority of Ascaris-specific T cells produced IL-4 (Th2) and, to a much lesser extent, IL-4/IFN-g (Th2/1 hybrids) or IFN-g alone (Th1). These data demonstrate that lung-stage but not the early liver-stage larvae lead to a locally restricted Th2 response. Significant Th2 cell accumulation in the small intestine occurs only when L4 complete the body migration. In addition, Th2 immunity seems to be hampered by the concurrent, nonspecific Th1 bias in growing pigs. Together, the late onset of Th2 immunity at the site of infection and the Th1- biased systemic immunity likely enable the establishment of intestinal infections by sufficiently large L4 stages and pre-adult worms, some of which resist expulsion mechanisms.